Forestry Decentralization in the Context of Global Carbon Priorities: New Challenges for Subnational Governments - Libert Amico, A.; Larson, A.M. (Frontiers Media, 2020)
The recent emphasis on the role of tropical forests in facing climate change has made forest decentralization debates more relevant than ever. Discussions on multilevel governance, polycentricity, and nested approaches to governance surround the central question, ever more pertinent considering global environmental change, of who holds the mandate over forests. Different levels of government, as well as private and civil society actors (companies, non-governmental organizations (NGOs), indigenous peoples, and local communities), compete over the rights of ownership, administration, and management of forest landscapes—decisions with a crucial impact on land use, land use change and the future of forests. Understanding the relations among different levels of governance, and government specifically, is essential to understand how carbon forestry has engaged with decentralization and the role of subnational governments (SNGs) in developing practical land use solutions. We draw on current trends in the forestry decentralization literature to ask: (i) has carbon forestry opened new opportunities for SNGs to support the sustainable governance of forest landscapes? (ii) have meaningful powers been assigned to SNGs in support of democratic processes of decision-making over forest landscapes? and (iii) is carbon forestry influencing the relationships between levels of government in a way that challenges unequal power relations? By examining carbon forestry projects and forestry decentralization processes across five countries (Indonesia, Mexico, Peru, Tanzania and Vietnam) with carbon forestry initiatives, we demonstrate how the role of SNGs is circumscribed by existing forestry decentralization trends. Decentralization initiatives in recent decades have provided SNGs with new mandates to manage forests, but new attributions do not always imply meaningful powers. The implementation of carbon forestry projects is molded by pre-existing power relations that shape the impacts of forestry decentralization on livelihoods and forest ecosystems. We find that carbon forestry, with both centralizing and decentralizing tendencies, operates within the spaces left by existing power dynamics that mold the way transfers of power are put into practice. Jurisdictional approaches will need to negotiate with this context to be able to push forward sustainable pathways.